2016
DOI: 10.1016/j.radonc.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Dose–volume effect relationships for late rectal morbidity in patients treated with chemoradiation and MRI-guided adaptive brachytherapy for locally advanced cervical cancer: Results from the prospective multicenter EMBRACE study

Abstract: Significant correlations were established between late rectal morbidity, overall and single endpoints, and dose-volume ( [Formula: see text] , [Formula: see text] ) and dose-point (D) parameters. A [Formula: see text] ⩽65Gy is associated with more minor and less frequent rectal morbidity, whereas a [Formula: see text] ⩾75Gy is associated with more major and more frequent rectal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(139 citation statements)
references
References 31 publications
8
128
1
2
Order By: Relevance
“…In a prospective trial of MR-guided brachytherapy (EMBRACE, international study on MRI-guided Brachytherapy in Locally Advanced Cervical Cancer) 23% of patients received a combined intracavitary/interstitial approach for at least one BT fraction. A follow-up analysis of rectal toxicities showed that the 3-year fistula risk was 12.5% with D2cc ≥ 75 Gy, and patients had a two-fold lower risk of proctitis with D2cc <65 Gy [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In a prospective trial of MR-guided brachytherapy (EMBRACE, international study on MRI-guided Brachytherapy in Locally Advanced Cervical Cancer) 23% of patients received a combined intracavitary/interstitial approach for at least one BT fraction. A follow-up analysis of rectal toxicities showed that the 3-year fistula risk was 12.5% with D2cc ≥ 75 Gy, and patients had a two-fold lower risk of proctitis with D2cc <65 Gy [5]. …”
Section: Introductionmentioning
confidence: 99%
“…39 The IGABT could optimize bowel dosimetry, especially for underweight patients with no or less intraabdominal fat, as the bowel loops are usually in very close proximity to the cervix and uterus. 18 Despite these limitations, the strength of this study was the inclusion of 245 patients treated with IMRT in a consistent fashion and a follow-up period of more than 5 years. Moreover, both clinical and dosimetric predictors of GI toxicity were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[63] have published the dose-volume effect relationship for late rectal morbidity of 960 patients treated in EMBRACE protocol. This data has to be compared cautiously with patients treated exclusively with a perineal IC/interstitial implant, mainly because of the bigger volumes of treatment in the last ones.…”
Section: Discussionmentioning
confidence: 99%